Carotenoid and chlorophyll profiles in five species of Malaysian seaweed as potential Halal Active Pharmaceutical Ingredient (API) - Othman, Rashidi; Md Amin, Nur Alifah; Abu Bakar, Ainaa Eliah (International Institute for Halal Research and Training (INHART), International Islamic University Malaysia, 2018)
Seaweed, also known as macroalgae, has been gaining the interest of researchers due to the presence of functional bioactive compounds that can be extracted from their biomass. This research aimed to explore the chlorophyll and carotenoid content from five species of Malaysian seaweed as potential Active Pharmaceutical Ingredient (API). Three species of red macroalgae (E. denticulatum, G. tikvahiae, and K. striatum), green macroalgae (C. lentillifera) and one brown macroalga (P. pavonica) were studied to determine their chlorophyll and carotenoid content by using UV-Vis spectrophotometer and HPLC. Their antioxidant properties were measured by using DPPH Radical Scavenging activity and antimicrobial activities were investigated by Disc Diffusion method. In terms of carotenoid content, P. pavonica contained the highest amount of carotenoid (100.89 ± 14.71 µg/g DW) and chlorophyll content (7.52 ±1.51 µg/g DW). Meanwhile, individual carotenoid content showed K. striatum had the highest lutein content (38.6 µg/g DW). Zeaxanthin, beta-carotene, and violaxanthin showed the highest amount in C. lentillifera at 21.30 µg/g DW, 10.70 µg/g DW, and 8.93 µg/g DW respectively. In addition, the antioxidant test showed that P. pavonica presented the strongest DPPH activity with the percentage of inhibition (i%) of (61.0% ± 0.9). Finally, strong antimicrobial activities were shown by seaweed samples toward E. coli and P. aerugenosa. All seaweed samples demonstrated moderate antifungal samples towards M. gypseum and Fusarium sp.